Canção e Dansa para Contrabaixo e Piano de Radamés Gnattali: estudo de aspectos técnico-interpretativos - Kilder Danjas (2008)
In Canção e Dansa, Brazilian composer Radamés Gnattali explores many idiomatic resources of the double bass, using a virtuosic writing still rarely employed in compositions for this instrument in Brazil (RODRIGUES, 2003, p.9). This study analyses the technical and interpretive aspects of double bass playing, such as bowings, fingerings, articulations, performance practices of erudite and of popular genres (aboio, baião and jazz) and effects through comparison of primary sources, namely editions (GNATTALI, 1934; GNATTALI, 1982; GNATTALI, 1985), recordings (GNATTALI, 1982; GNATTALI, 1996; GNATTALI, 1999) and interviews with musicians related to the history of the work (GNATTALI, 2003; SBRAGIA, 2003). The sophisticated idiomatic writing employed by Gnattali in this historical landmark for double bass and piano of 1934 results in compositional language that mixes folkloric and virtuosic elements, allowing for the integration of popular and classical elements.